Snapshots. Images, Crowds, Thoughts. A Conversation With Susan Buck-Moss - Fernández Polanco, Aurora (Re-visiones, 2024)
This conversation was prompted by the interest of our research project in all the people (in the theoretical field as well as in artistic or curatorial practices) who carry out what we have called a thought through images. In this sense, more than unquestionable, Susan Buck-Morss’s figure was foundational. We were especially interested in picking up some Benjaminian derivations that have accompanied her since the issue of her book The Dialectics of Seeing, a critical visuality with which it is possible to politically rethink hegemonic narratives, as is the case of Dreamworld and Catastrophe. The Passing of Mass utopia in East and West; Hegel, Haiti, and Universal History or Thinking Past Terror: Islamism and Critical Theory on the Left. The conversation will be interwoven with this factory of thought that regards the image as a fundamental tool of political theory, with all that is implied –for the emergence of a new culture– in the possibility of sharing it (Visual Studies and Global Imagination, 2004). The events that went off like simultaneous powder kegs –Arab spring, 15-M, occupy movements, etc.– true devices of bodies, words, images and gestures, proved that this new culture would also favor the emergence of a new policy, the potency (not the power) of what she has called the translocal commons (On Translocal Commons and the Global Crowd, 2013). The conversation took place in New York, in March 2014.